2004
DOI: 10.1517/14656566.5.6.1257
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of Ewing sarcoma family of tumours

Abstract: The Ewing sarcoma family of tumours comprises of a group of well-characterised neoplasms with aggressive behaviour. Despite significant progress with the use of intensive multiagent chemotherapy and local control measures, a significant proportion of patients die because of disease progression. Most treatment regimens are based on the intensification of alkylating agents and topoisomerase-II inhibitors. Using this approach, the expected survival rate is between 70 and 80% in patients with localised disease. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…These five consecutive institutional studies recapitulate the incremental advances made internationally in the management of ESFT [11][12][13][14]. Treatments built on the efficacy of the four-drug regimen used in ES79 [5] by first adding the ifosfamide-etoposide (IE) combination (EW87) [6] and then intensifying therapy, adding granulocyte colony-stimulating factor, and improving support measures (EWI92, SJBCM and HIRISA) [2,15]. As systemic approaches evolved, so did local control.…”
Section: Discussionmentioning
confidence: 99%
“…These five consecutive institutional studies recapitulate the incremental advances made internationally in the management of ESFT [11][12][13][14]. Treatments built on the efficacy of the four-drug regimen used in ES79 [5] by first adding the ifosfamide-etoposide (IE) combination (EW87) [6] and then intensifying therapy, adding granulocyte colony-stimulating factor, and improving support measures (EWI92, SJBCM and HIRISA) [2,15]. As systemic approaches evolved, so did local control.…”
Section: Discussionmentioning
confidence: 99%
“…These two components are carried out in three phases: (1) induction chemotherapy, the goal of which is to achieve rapid initial cytoreduction and facilitate local control, (2) local control using surgery, radiation therapy, or both, usually after 10-12 weeks of induction chemotherapy, and (3) continuation therapy, which consists of chemotherapeutic regimens similar to those used for induction. 97 …”
Section: Therapy and Clinical Outcome Therapymentioning
confidence: 99%
“…6). 10,97 Furthermore, pelvic ESFT is commonly insidious and patients tend to present later in the disease course with advanced-stage disease. In one study, 25% of patients with primary pelvic ESFT had metastasis at diagnosis compared with 16% for patients with tumors arising at other sites.…”
Section: Outcome and Prognostic Factorsmentioning
confidence: 99%
“…This dose intensification and interval compression has the theoretical advantage of allowing less time for recovery of the partially resistant cells. The efficacy of interval compression is currently being evaluated by the Children's Oncology Group (COG) AEWS-0031 study [16].…”
Section: Systemic Treatment: Chemotherapy Evolution Of Chemotherapeutmentioning
confidence: 99%
“…Treatment regimens using high doses of alkylating agents or topoisomerase II inhibitors (etoposide) have been associated with a high cumulative incidence of treatment-related acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS) [1,16]. The incidence in most studies has been reported to be approximately 8%, however up to a 22.7% incidence was noted in a small study of high-risk patients treated with very high-dose chemotherapy [17][18][19].…”
Section: Systemic Treatment: Chemotherapy Evolution Of Chemotherapeutmentioning
confidence: 99%